Exposure to suppressive antibiotic therapy in women with recurrent urinary tract infections and severity of infections: a retrospective population-based cohort study - Ana Moragas; Rosa Morros; Dan Ouchi; Carl Llor; Maria Giner-Soriano; Silvia Fernández-García (BMJ Open)
Background Women with recurrent urinary tract infections (UTIs) often undergo intensive antibiotic exposure, especially with suppressive therapies. Suppressive therapy is recommended for women with three UTIs in the past year or two in the last 6 months. However, the collateral long-term effects of this have been poorly studied.Objectives To assess whether suppressive therapy for recurrent UTIs increases the incidence and severity of future infections compared with episodic UTI treatment.Design Retrospective cohort study.Setting and Participants The study was conducted using data from the Information System for Research in Primary Care database, including 5.8 million people in Catalonia. Two groups of women with recurrent UTIs (≥3 episodes/year) were compared: those on suppressive antibiotic therapy for ≥6 months and those treated episodically. Primary outcomes were hospitalisations due to pyelonephritis, septicaemia, COVID-19, influenza, pneumonia and mortality by these infections, over a 100-month follow-up period.Results Among 36 170 women, 2898 (8%) were treated with continuous suppressive therapy. Overall, 6.9% of the population experienced severe infections, with a higher incidence in women on suppressive therapy (12.6%) compared with those without (6.4%), with a HR of 1.50 (95% CI 1.33 to 1.68). Pyelonephritis presented the greatest difference (HR, 1.95 (95% CI 1.64 to 2.33)), followed by septicaemia (HR, 1.34 (95% CI 1.13 to 1.59)) and COVID-19 (HR 1.23 (95% CI 1.01 to 1.50)).Conclusions Suppressive antibiotic therapy in women with recurrent UTIs is associated with a higher incidence and severity of future infections. Future research should focus on clarifying causal relationships and identifying the potential mechanisms involved.